Audit committee characteristics and firm financial performance of quoted industrial goods firms in Nigeria - Abu, Samuel Enejoh (Goodwood Publishing, 2024)
Purpose: This study examines the effects of audit committee characteristics on the financial performance of listed industrial goods firms in Nigeria. Research methodology: This study used an ex-post factor research design and utilized secondary data collected from the annual reports and accounts of thirteen (13) sampled industrial goods firms for a period of 10 years (2013-2022). The sample of firms was obtained using a purposive sampling technique. Data were analyzed using descriptive statistics, correlation, and regression analysis (GLS Random Effect) with the aid of Stata 13. Results: The findings reveal that an insignificant positive effect exists between audit committee size and financial performance (ROA and ROE), while audit committee independence has a significant negative effect on return on assets (ROA) and a negative insignificant effect on return on equity (ROE), and audit committee meetings have a positive significant effect on asset (ROA) and a positive insignificant effect on return on equity (ROE). Limitations: The research is limited to only those companies in the industrial goods sector listed on the Nigerian Stock Exchange from 2013 to 2022 and only focuses on the effect of audit committee characteristics on firm financial performance. There was also incomplete data, which did not allow for a complete and thorough analysis of the entire sector. Contribution: This study contributes to the existing body of literature on the effect of audit committees on the financial performance of Nigeria’s listed industrial goods sector. It provides insights that can assist the board in formulating appropriate strategies to improve their performance.